False connections: systems and action theories in neofunctionalism and in Jürgen Habermas - Schwinn, Thomas (Sociological theory, 1998)
Recent theoretical discussions have served to bridge the gap separating systems- and action-theoretical approaches; however, the question of their basic compatibility has rarely been raised. This paper takes up two efforts at linking systems and action theory: those of neofunctionalists and those of Jürgen Habermas. Neofunctionalists start from the inadequacies of systems functionalism and seek to open it to the theory of action. Habermas, on the other hand, seeks to overcome the limits of the theory of action by widening its scope in systems-theoretical terms. Successful synthesis eludes both efforts: either the status of voluntaristic aspects is so enhanced that the systemic whole and its functional imperatives practically vanish, or too much emphasis is placed on the systemic aspect, reducing actors to the mere executing agents of systemic needs. The combination of theories of structure and action provides a way out of this dilemma.